Integrating Maqasid al-Shariah, Science, and State Regulation: A Multidisciplinary Framework for Muslim Children's Protection in Digital Environments - Vebionita Megi Putri; Silvia Novi Yanti (Suluah Pasaman, 2026)
Digital technology expansion presents both opportunities and significant risks for children, particularly regarding exposure to inappropriate content and harmful online interactions. Child protection in digital environments demands a comprehensive approach integrating religious, scientific, and policy dimensions. This study develops a multidisciplinary framework through three converging perspectives: Maqasid al-Shariah as a normative Islamic foundation, empirical findings from neuroscience and communication science on social media's impact on children's cognitive and psychosocial development, and Indonesian national regulations—particularly Permen Komdigi No. 9 of 2026 restricting social media access for children under 16 years. A qualitative design employing integrative literature review and thematic content analysis was adopted. Findings demonstrate that hifdz al-'aql (protection of intellect) and hifdz al-nasl (protection of progeny) are the most operationally relevant Maqasid principles for digital child protection. Scientific evidence consistently confirms negative impacts of excessive screen time on brain development and mental health, while state regulation provides the operational mechanism for enforcement. The integration of Islamic values and scientific evidence substantially strengthens regulatory legitimacy and effectiveness, creating dual normative and empirical foundations for a safe digital ecosystem for Muslim children in Indonesia